Hubungan Penggunaan Media Sosial dengan Sikap Anti-cyberbullying pada Siswa SMP di Banjarmasin - Akhmad Fadillah Fahriannor; Nina Permata Sari; Noor Ainah (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study aims to examine the relationship between social media use and anti-cyberbullying attitudes among junior high school students. Methods – This research employed a quantitative approach using a cross-sectional survey design. The sample consisted of 121 seventh-grade students of SMP Negeri 13 Banjarmasin selected through purposive sampling. Data were collected using self-administered questionnaires measuring social media use and anti-cyberbullying attitudes. Social media use was operationalized as a multidimensional construct, including intensity, types of activities, socio-emotional experiences, and online interaction norms. Data was analyzed using Pearson correlation and simple linear regression with the assistance of SPSS 29, after fulfilling assumption tests including normality and linearity. Findings – The results showed a significant positive relationship between social media use and anti-cyberbullying attitudes (r = 0.442; p < 0.001), indicating a moderate level of association. Regression analysis further revealed that social media use significantly contributes to anti-cyberbullying attitudes (? = 0.359; p < 0.001), with a coefficient of determination (R²) of 0.196. This indicates that social media use accounts for 19.6% of the variance in anti-cyberbullying attitudes. These findings suggest that social media use is associated with the development of preventive attitudes toward cyberbullying, without implying a causal relationship.Research Implications – This study highlights the importance of digital interaction experiences in shaping adolescents’ preventive attitudes toward cyberbullying. However, the findings should be interpreted with caution due to the cross-sectional design, single-site sample, and reliance on self-reported data, which may introduce bias.